2019
DOI: 10.3390/ma13010064
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of Composites with Recycled Cement Mortar Used as a Supplementary Cementitious Material

Abstract: The process of recycling concrete rubble is accompanied by the formation of a large amount of fine fraction, which cannot be reused as aggregate. The results of research on the possibility of using recycled cement mortar (RCM), obtained during concrete recycling, as a cementitious supplementary material, are presented. The experimental research was carried out on the basis of two variables determining the recycling process: X 1 -temperature (range of variation 288-712 • C) and X 2 -time (range of variation 30-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Some authors simply concentrated on a single treatment temperature [ 5 , 6 ] and others approached only a few properties, namely the fresh behavior and the mechanical strength [ 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Other studies were dedicated to the incorporation of varying percentages of RC in mortars and concrete [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Furthermore, results reported in the literature are contradictory, reflecting the lack of knowledge of these poorly explored new binders [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors simply concentrated on a single treatment temperature [ 5 , 6 ] and others approached only a few properties, namely the fresh behavior and the mechanical strength [ 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Other studies were dedicated to the incorporation of varying percentages of RC in mortars and concrete [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Furthermore, results reported in the literature are contradictory, reflecting the lack of knowledge of these poorly explored new binders [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…properties of modified cement matrix composites reinforced with fibers [14,[18][19][20]; • application of new types of supplementary cementitious materials [13,16,[21][22][23][24][25][26][27][28]; • characterization of various types of modified cement based materials [18,21,23,[25][26][27][28][29][30][31].…”
Section: Short Description Of the Articles Presented In This Special Issuementioning
confidence: 99%
“…The issues of the original research papers and stat-of-the art reviews published in this Special Issue of Materials, and coming from over 45 international universities and scientific centres, can be divided as follows: permeability and diffusivity, which are directly related to the quality of concrete and to the durability in various aggressive environments [ 13 , 14 , 15 , 16 , 17 ]; properties of modified cement matrix composites reinforced with fibers [ 14 , 18 , 19 , 20 ]; application of new types of supplementary cementitious materials [ 13 , 16 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]; characterization of various types of modified cement based materials [ 18 , 21 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. …”
Section: Short Description Of the Articles Presented In This Special Issuementioning
confidence: 99%
“…In recent years, the attention has shifted towards the production of recycled cement (RC) with rehydration capacity through thermal activation [1,4]. In this still relatively unexplored domain, studies have mostly focused on the microstructure and rehydration behaviour of RC [5][6][7][8][9][10], as well as the mechanical characterisation of cement pastes and mortars produced with this binder [11][12][13][14][15][16][17][18]. RC pastes have been reported to achieve compressive strengths of up to 32 MPa at 28 days [7], though generally presenting high water demand and low setting times [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Kalinowska-Wichrowska et al [15] investigated the influence of the treatment temperature and residence period on the mechanical strength of mortars with 25% RC obtained from the cement fraction of waste mortar. The authors found that the incorporation of RC treated at 650 • C for 80 min led to the highest compressive strength.…”
Section: Introductionmentioning
confidence: 99%